2012
DOI: 10.7202/1012539ar
|View full text |Cite
|
Sign up to set email alerts
|

Unions and Temporary Help Agency Employment

Abstract: Temporary help agency employment (THAE) is a peculiar and often precarious employment form that has become increasingly salient in Canada in recent decades. Seeking to advance both the literatures on precarious work and union renewal, this article examines the effects of the expansion of this unique employment form upon labour unions, and union responses to this phenomenon.The study employed a qualitative exploratory method, involving twenty-four interviews with key informant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…Power imbalances between TWA employees and their permanent colleagues constitute a first issue in the development of an established-outsider figuration. Compared to permanent workers, TWA employees often experience difficulties in standing up for their rights Padavic, 2005) and are less likely to have a say at their workplace, both individually (Hall, 2006;Kirkpatrick & Hoque, 2006;Winkler & Mahmood, 2015) or through union representation (Bartkiw, 2012;Byoung-Hoon & Frenkel, 2004). Second, there is evidence that permanent workers use stigmatisation practices because they sometimes perceive temporary agency workers as a threat to their own positions (Boyce et al, 2007;Crocker, Major, & Steele, 1998).…”
Section: Established-outsider Relations In the Context Of Temporary Amentioning
confidence: 99%
“…Power imbalances between TWA employees and their permanent colleagues constitute a first issue in the development of an established-outsider figuration. Compared to permanent workers, TWA employees often experience difficulties in standing up for their rights Padavic, 2005) and are less likely to have a say at their workplace, both individually (Hall, 2006;Kirkpatrick & Hoque, 2006;Winkler & Mahmood, 2015) or through union representation (Bartkiw, 2012;Byoung-Hoon & Frenkel, 2004). Second, there is evidence that permanent workers use stigmatisation practices because they sometimes perceive temporary agency workers as a threat to their own positions (Boyce et al, 2007;Crocker, Major, & Steele, 1998).…”
Section: Established-outsider Relations In the Context Of Temporary Amentioning
confidence: 99%
“…La penetración sindical en las agencias intermediarias de empleo constituye una tarea muy difícil y problemática en todos los sistemas de relaciones laborales 7 y la intermediación laboral complica considerablemente la acción sindical (Bartkiw, 2012). Los breves períodos a lo largo de los cuales los trabajadores son puestos disposición constituyen, desde luego, una dificultad no menor.…”
Section: Ideas Preliminaresunclassified
“…Y para poder presentar su candidatura se requieren seis meses de prestación de servicios. Por lo demás, la negociación colectiva aborda temas como la utilización del crédito de horas o el período máximo entre cesiones que no extingue el 13 Describiendo la experiencia canadiense, Bartkiw (2012), p. 471. mandato representativo de los trabajadores de estas agencias. Incluso se observa la posibilidad de que se utilicen horas de representación durante los períodos entre puestas a disposición.…”
Section: Modelos De Representación De Los Trabajadores De Agencias Prunclassified
“…Arrowsmith (), too, argues that union initiatives are important when it comes to drawing attention to temporary agency workers' conditions, for example via different measures aimed at facilitating union representation and via political campaigns. A Canadian qualitative study of union responses to the temporary agency industry found that little efforts were made to address the specific needs of temporary agency workers (Bartkiw, ). Rather, the unions' response was characterised as ‘incremental adjustments aimed at shoring up collective bargaining arrangements normalized by past practice, culture, and/or the legal regime’ (Bartkiw, : 471).…”
Section: Previous Research and Theoretical Departure Pointsmentioning
confidence: 99%
“…A Canadian qualitative study of union responses to the temporary agency industry found that little efforts were made to address the specific needs of temporary agency workers (Bartkiw, ). Rather, the unions' response was characterised as ‘incremental adjustments aimed at shoring up collective bargaining arrangements normalized by past practice, culture, and/or the legal regime’ (Bartkiw, : 471).…”
Section: Previous Research and Theoretical Departure Pointsmentioning
confidence: 99%